DETERMINING INCOME INEQUALITY IN INDONESIA: THE ROLE OF ACCESS TO ELECTRICITY, GDP PER CAPITA, AND EDUCATION - Nabila Assyifa; Toto Gunarto; Asih Murwiati (ZILLZELL MEDIA PRIMA, 2025)
Income inequality between regions is one of the main challenges in economic development in Indonesia. This study aims to analyze the effect of electricity access, Gross Regional Domestic Product (GDP) per capita, and average length of schooling on income inequality in 34 provinces in Indonesia in the 2015–2023 period. Using a panel data regression approach with the Fixed Effect Model (FEM), the results showed that simultaneously the three independent variables had a significant effect on income inequality. However, partially, only GDP per capita and average length of schooling have a negative and significant influence, while access to electricity has no significant effect. These findings show that increasing regional income and community education can reduce the income gap between regions. Meanwhile, electrification has not had a direct impact on income equity without the support of other supporting infrastructure. This research emphasizes the importance of inclusive economic development and equitable access to education as the key to reducing inequality in Indonesia.